2014
DOI: 10.1186/1755-7682-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Fractal correlation property of heart rate variability in response to the postural change maneuver in healthy women

Abstract: BackgroundWe evaluated the effects of the PCM on the fractal analysis of the HRV in healthy womenMethodWe evaluated healthy women between 18 and 30 years old. HRV was analyzed in the time (SDNN, RMSSD, NN50 and pNN50) and frequency (LF, HF and LF/HF ratio) domains as well as short and long-term fractal exponents (alpha-1 and alpha-2) of the detrended fluctuation analysis (DFA). HRV was recorded at rest for ten minutes at seated rest and then the women quickly stood up from a seated position in up to three seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
2
10
1
4
Order By: Relevance
“…We showed that ( , ) of IBI decreases with in healthy individuals sitting at rest, from values typical for fractional Brownian motions to values typical for fractional Gaussian noises. A similar behavior has been previously observed in other studies that applied DFA with traditional monofractal approaches (i.e., with = 2 only) to analyze the heart-rate variability in sitting volunteers at rest [16,28]. A possible explanation for this trend has been already proposed, based on the hypothesis that the heart-rate dynamics depend on the superposition of two fractal processes simultaneously modulating the heart rate [7,29].…”
Section: Discussionsupporting
confidence: 53%
“…We showed that ( , ) of IBI decreases with in healthy individuals sitting at rest, from values typical for fractional Brownian motions to values typical for fractional Gaussian noises. A similar behavior has been previously observed in other studies that applied DFA with traditional monofractal approaches (i.e., with = 2 only) to analyze the heart-rate variability in sitting volunteers at rest [16,28]. A possible explanation for this trend has been already proposed, based on the hypothesis that the heart-rate dynamics depend on the superposition of two fractal processes simultaneously modulating the heart rate [7,29].…”
Section: Discussionsupporting
confidence: 53%
“…The subject remained seated at rest with spontaneous breathing. After 10 min the volunteers quickly stood up from a seated position in up to three seconds according to verbal command and remained standing for 10 min (de Souza et al, 2014). Heart rate variability (HRV) was analyzed at two moments: 10 min seated rest with spontaneous breathing, and 10 min at standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Normal HRV activity in response to postural change reflects a shift from parasympathetic predominance at rest to sympathetic control while standing (de Souza et al, 2014). Some studies have reported an attenuated or absent HRV response to postural change in subjects with chronic diseases such as hypertension and diabetes , suggesting that autonomic impairment and early sympathetic dysfunction may be present in such individuals.…”
Section: Introductionmentioning
confidence: 97%
“…Souza et al [8] (2014) evaluated healthy women aged 18-30 years studying the behavior of HRV in response to the postural change maneuver, using linear and nonlinear variables. They observed that the short-term alpha-1 exponent was significantly increased at all moments investigated compared to seat.…”
Section: Topic Highlightmentioning
confidence: 99%